SPATIAL POINT PATTERN ANALYSIS OF AVAILABLE TO STUDY THE MIXED FOREST STANDS MOVEMENT IN ATROOSH REGION - Al-Bag, Muzahim S.; Mohammed, Ammar J.; Kero, Shamsaldeen M. (Diyala Agricultural Sciences Journal, 2017)
Spatial patterns of species at different life stages are an important aspect for understanding causal mechanisms that facilitate species co-existence. Using Ripley's univariate L(r) and bivariate L12 functions, we analyzed the spatial patterns of two canopy species at different life stages in mixed forest in Atroosh egion. By using program PASSAGE V.2, the analysis of L(r) function for species (a) and the three age class appear regular pattern population, since the type species ( b ) appear light cluster pattern, the relationship between two age classes for different species appear positive relate, we show the hardly positive relation appear to L(12) function between the age aj-bm, am-bm, but the negative appear in three pairs between the age aj-am, ap-am, aj-ap. The growth and develop of age class (aj) effected of different age class, we believe decreases of number in age class (aj) result of high competition among the different stages of age. The relation between species (a, b) for general is positive, both species growth and develop at presence of the other, we believe the two species dominance in Atroosh forest stay for a long time.